2015
DOI: 10.1097/qai.0000000000000667
|View full text |Cite
|
Sign up to set email alerts
|

HIV and Sexually Transmitted Infection Incidence and Associated Risk Factors Among High-Risk MSM and Male-to-Female Transgender Women in Lima, Peru

Abstract: Background Men who have sex with men (MSM) and male-to-female transgender women (TW) are at increased risk of HIV and sexually transmitted infections (STIs). We evaluated factors associated with incidence of HIV, HSV-2, and chlamydia and gonorrhea (anal and pharyngeal). Methods We used data from the Comunidades Positivas trial with MSM/TW who have sex with men in Lima, Peru. Participants were asked about sexual risk behaviors and underwent HIV/STI testing at baseline and 9- and 18-month follow-ups. We used d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
67
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 24 publications
6
67
2
Order By: Relevance
“…43 Another study conducted in Bangkok observed an overall HIV incidence of 5.9 per 100 person-years from 2006 to 2012, 44 whereas in northern Thailand, HIV incidence among a cohort 45 In a cohort of 510 MSM in Lima, Peru, the HIV incidence was 4 cases per 100 person-years, further indicating high risk as compared with other adults. 36 Furthermore, a 2012 review of 55 studies among MSM in China found a dramatic 3.3-fold increase in HIV incidence among MSM from 2.04 to 7.02 per 1000 person-years during 2002-2010. 46 Taken together, these data suggest that HIV incidence is more similar than different across varying income levels of countries.…”
Section: Current Hiv Incidence Data Among Men Who Have Sex With Men Imentioning
confidence: 99%
“…43 Another study conducted in Bangkok observed an overall HIV incidence of 5.9 per 100 person-years from 2006 to 2012, 44 whereas in northern Thailand, HIV incidence among a cohort 45 In a cohort of 510 MSM in Lima, Peru, the HIV incidence was 4 cases per 100 person-years, further indicating high risk as compared with other adults. 36 Furthermore, a 2012 review of 55 studies among MSM in China found a dramatic 3.3-fold increase in HIV incidence among MSM from 2.04 to 7.02 per 1000 person-years during 2002-2010. 46 Taken together, these data suggest that HIV incidence is more similar than different across varying income levels of countries.…”
Section: Current Hiv Incidence Data Among Men Who Have Sex With Men Imentioning
confidence: 99%
“…26,29 Understanding the factors impeding HIV testing is crucial because nearly 70% of participants with HIV in Lima were unaware of their positive serostatus. 39 This is often attributed to high testing-related stigma. 23 Education about AHI and the provision of AHI testing could ultimately reduce fear and stigma about HIV/AIDS, if early infection was marketed as an opportune time to initiate treatment, especially considering the high infectious potential.…”
Section: Discussionmentioning
confidence: 99%
“…That proportion, lower than figures from surveillance studies (62.5–90%), is similar to figures reported in other studies in STI clinics (28.8–30.0%). [6,1619] However, it is important to recognize that due to the inclusion criteria of our cohort study favoring MSM and transgender women at higher risk of HIV and syphilis, the estimation of undiagnosed HIV-infection may not be representative.…”
Section: Discussionmentioning
confidence: 99%
“…[6,16,17] In contrast, studies occurring at STI clinics, where HIV testing is often sought after or recommended, have found rates of HIV-serostatus unawareness <30%. [18,19] …”
Section: Introductionmentioning
confidence: 99%